APA Handbook of Community Psychology: Methods for Community Research and Action for Diverse Groups and Issues. 2017
DOI: 10.1037/14954-037
|View full text |Cite
|
Sign up to set email alerts
|

Educating community psychologists in a changing world.

Abstract: The history of community psychology around the globe has been influenced by context, values, and theoretical concepts and methods (Francescato, 2009;

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…These guidelines define the quality of higher education in Europe indicating that psychologists' skills reveal only expertise, and rely on a marketing model to some extent, which is thus sometimes very unlike the participatory model in which the consumer and community psychologist support something resembling a common competence, to be able to change people's living circumstances. Attempts have been made to define CP competences (e.g., Dalton & Wolfe, ) which do not correspond well with the Europsy guidelines (Francescato, & Zani, 2013; Hazel, ; Serrano‐García, Pérez‐Jiménez, & Rodríguez‐Medina, ).…”
Section: Resultsmentioning
confidence: 99%
“…These guidelines define the quality of higher education in Europe indicating that psychologists' skills reveal only expertise, and rely on a marketing model to some extent, which is thus sometimes very unlike the participatory model in which the consumer and community psychologist support something resembling a common competence, to be able to change people's living circumstances. Attempts have been made to define CP competences (e.g., Dalton & Wolfe, ) which do not correspond well with the Europsy guidelines (Francescato, & Zani, 2013; Hazel, ; Serrano‐García, Pérez‐Jiménez, & Rodríguez‐Medina, ).…”
Section: Resultsmentioning
confidence: 99%
“…Considering that our field in the United States is 50 years old, there are relatively few publications explicitly about training and education (see the following articles: Alcalde & Walsh‐Bowers, ; Balch & McWilliams, ; Bennett et al., ; Glenwick & Busch‐Rossnagel, ; Iscoe et al., ; Kelly, ; Libo, ; McMahon, Jimenez, Bond, Wolfe & Ratcliffe, ; Meyers, ; Seidman & Rappaport, ; Serrano‐Garcia, Pérez‐Jiménez & Rodríguez‐Medina, ; Walfish, Polifka & Stenmark, ; Weinstein, ). This is remarkable given the importance of education and training in addressing the broader goals of the field (e.g., Iscoe et al., ).…”
Section: Historical Overview Of Education and Training In Community Pmentioning
confidence: 99%
“…In addition, Serrano‐Garcia et al. () critical analysis of CP education revealed that most programs are not engaged in pedagogical practices aligned with the values of the field. Serrano‐Garcia et al.…”
Section: Historical Overview Of Education and Training In Community Pmentioning
confidence: 99%
See 2 more Smart Citations